Neutrophil-to-lymphocyte ratio as predictor of outcome in acute pancreatitis - Saha, Dipanwita; Sutradhar, Probir Kumar; Alam, Md Shafiul; Saha, Anita; Karim, A S M Bazlul (Northern International Medical College Journal, 2025)
Background : Acute pancreatitis (AP) is a commonly encountered emergency in children. It has always been tough to predict accurately among the AP patients who will become progressively unwell. Simple prognostic marker such as neutrophil-to-lymphocyte ratio (NLR) could identify such patients. This study was done to assess the usefulness of this marker in case of clinic AP. Methods : This Cross-sectional descriptive study was conducted from July 2018 to June 2020 at the department of Pediatric Gastroenterology and Nutrition, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. Thirty-one children with abdominal pain aged between 3-15 years diagnosed as acute pancreatitis as per INSPPIRE criteria were included in this study. The detailed clinical history, physical examination findings and investigation reports were recorded in a predesigned standard data sheet. Complete blood count (CBC) report from each patient on admission was obtained which included white blood cell (WBC) count with differentials, Neutrophil-to-lymphocyte ratio (NLR) was measured manually by using the absolute value of neutrophil and lymphocyte. Outcomes of acute pancreatitis were observed in terms of cure or survival or mortality. Data was analyzed by SPSS version 25. All continuous variables were presented as mean. For all statistical tests p< 0.05 was considered statistically significant. Results : The mean age of the patients was 11.19 (±3.45) years. The mean neutrophil-to-lymphocyte ratio (NLR) was 4.49 (±3.99). Total thirty patients (97%) were recovered and one patient (3%) expired during hospital stay. Thirteen patients (41.9%) developed complications among which ascites were most common, present in 12(38.7%). Eighteen patients had no complications among them 15 patients were with NLR<5. A total of 9 patients had complications among them 6 (46.2%) were with NLR ≥5. Mean length of hospital stay (LOS) for NLR<5 group was 9.32 days while that mean was 9.78 days for ≥5 NLR group. Conclusion : It was found that elevated NLR on admission had an unfavorable clinical outcome for pediatric patients with acute pancreatitis (AP) although statistical significance could not be established. Therefore, multicenter studies with larger sample size are required for making some clinically applicable inference. Northern International Medical College Journal Vol. 14 No. 1-2 July 2022-January 2023, Page 639-642